Social sustainability indicators as performance. Issue 103 (July 2019) - Hale, James; Legun, Katharine; Campbell, Hugh; Carolan, Michael
Abstract: We are living in an era of the audit. Sustainability indicators are used to ensure that industries are behaving responsibly. The audits are well elaborated in their environmental requirements, but they are often less directly engaged with issues of social sustainability. Should they be? After describing a number of challenges with measuring social sustainability, this paper defends representing social sustainability through indicators by taking a performative orientation toward them. Here, we suggest holding a relationally real analytical stance about what contributes to more equitable and diverse assembling processes. In iteratively doing so, we can work to determine indicators that are less focused upon the practices they are meant to represent, and more on their potential impact on intended audiences. In other words, this takes up the suggestion that indicators are themselves agents and then takes this a couple of steps further by arguing for the potential work social scientists can do using indicators to move toward better futures. We ground this theorizing in two short vignettes taken from the authors' work in food and agriculture cooperatives and also in a fruit industry.